Why the light changes direction in entering the water - Fassihi, Mohammad (IJRDO-Journal of Applied Science, 2016)
Confined Quantum Field Theory, gives a simpler and at the same time strongerformulation of the elements of physics. Therefore it suggests that we give to the studentsalready from the beginning the simple formulation that comes from this basic theory